Quantitative Analysis of Gravity Currents Using the Light Attenuation Technique - Tjung, Ezra Yoanes Setiasabda; Kikkert, Gustaaf Adriaan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
It is well known that when two fluids with different specific densities are put adjacent to each other, there is an unbalanced horizontal density gradient that results in the adjustment process to achieve equilibrium, so that the less dense fluid finds its way atop the denser fluid. The purpose of this study is to employ light attenuation technique to obtain quantitative data in investigating the mentioned phenomenon. Specifically, the gravity current experiment models what is commonly found in estuaries, where there is an unbalanced density gradient due to the different densities of saltwater and fresh water. The use of light attenuation technique enables a more accurate quantitative data collection and thus enables a more rigorous definition of the location of the nose and the thickness of the head to be applied during the analysis of experimental data. It also allows for investigating the mixing characteristics of the two fluids in the highly turbulent layer immediately behind the current head process such as the velocity and the thickness of the shear layer